2010
DOI: 10.1002/jbmr.283
|View full text |Cite
|
Sign up to set email alerts
|

Camurati-engelmann disease: Unique variant featuring a novel mutation in TGFβ1 encoding transforming growth factor beta 1 and a missense change in TNFSF11 encoding RANK ligand

Abstract: We report a 32-year-old man and his 59-year-old mother with a unique and extensive variant of Camurati-Engelmann disease (CED) featuring histopathological changes of osteomalacia and alterations within TGFβ1 and TNFSF11 encoding TGFβ1 and RANKL, respectively. He suffered leg pain and weakness since childhood and reportedly grew until his late 20s, reaching 7 feet in height. He had deafness, perforated nasal septum, torus palatinus, disproportionately long limbs with knock-knees, low muscle mass, and pseudoclub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 72 publications
3
33
0
Order By: Relevance
“…Serum LDH levels were normal in 6 adult patients at Washington University representing skeletal fluorosis (26,27) (2), hepatitis C-associated osteosclerosis (28) (2), and LRP5 high bone mass (29) (1) and low (75 U/L; normal 100 to 190 U/L) in a man with a unique variant of Camurati-Engelmann disease (30) (1). The 41 Shriners patients and 6 adult patients had unremarkable serum AST and ALT levels.…”
Section: Osteopetrosis (Alt Ald Ck-bb and Tracp-5b Values)mentioning
confidence: 99%
“…Serum LDH levels were normal in 6 adult patients at Washington University representing skeletal fluorosis (26,27) (2), hepatitis C-associated osteosclerosis (28) (2), and LRP5 high bone mass (29) (1) and low (75 U/L; normal 100 to 190 U/L) in a man with a unique variant of Camurati-Engelmann disease (30) (1). The 41 Shriners patients and 6 adult patients had unremarkable serum AST and ALT levels.…”
Section: Osteopetrosis (Alt Ald Ck-bb and Tracp-5b Values)mentioning
confidence: 99%
“….Mutations of this gene result in increased transforming growth factor activity and subsequent stimulation of osteoblastic bone formation. Also, although these mutations were originally thought to result in suppression of the osteoclastic bone resorption, newer evidence suggests that they may actually promote the formation and activity of osteoclasts 3,4 . CED is characterized by progressive expansion and sclerosis, especially along the shafts of the long bones,-and typically presents in childhood with generalized muscle weakness, lower limb pain, as well as a waddling gait 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Two other families previously were reported to have such a duplication, but interestingly, in this patient the duplication counts 12 nucleotides instead of the previously reported 9 nucleotides. (4) Whyte et al's report (1) shows many similarities to tandem duplications found in the signal peptide of the RANK protein. Closely related but clearly distinguishable phenotypes were associated with duplications of different size in that part of the gene encoding RANK.…”
mentioning
confidence: 99%
“…I n the current issue, Whyte et al describe a mother and son diagnosed with Camurati-Engelmann disease (CED), (1) a sclerosing bone disease caused by mutations in the transforming growth factor b1 (TGF-b1) gene. (2,3) Interestingly, both patients show major differences in their phenotype.…”
mentioning
confidence: 99%
See 1 more Smart Citation